1991
DOI: 10.1161/01.hyp.17.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin response in collecting ducts of rats resistant to mineralocorticoid hypertension.

Abstract: In previous studies we found that vasopressin stimulation of both cyclic AMP (cAMP) formation in cortical collecting tubules (CCT) and sodium reabsorption in isolated perfused kidneys was markedly exaggerated in rats with mineralocorticoid hypertension. In the present study, we tested the response (cAMP accumulation) of cortical and outer medullary collecting tubules (OMCT) to vasopressin in two rat models that are resistant to deoxycorticosterone acetate (DOCA) -induced hypertension, the Wistar-Furth strain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…Similar changes to renal structure have been reported by others. 21 The DOCA-salt-treated animals had elevated plasma sodium and osmolality levels, which is consistent with the observations that this model of hypertension is associated with increased renal sodium and water reabsorption 22 and with expansion of extracellular fluid volume. 23 The hypertensive animals also had elevated plasma AVP levels, a finding that has been reported previously by others 1 -2 and is probably due to an increased synthesis of AVP in the supraoptic and paraventricular nuclei of the hypothalamus.…”
Section: Resultssupporting
confidence: 87%
“…Similar changes to renal structure have been reported by others. 21 The DOCA-salt-treated animals had elevated plasma sodium and osmolality levels, which is consistent with the observations that this model of hypertension is associated with increased renal sodium and water reabsorption 22 and with expansion of extracellular fluid volume. 23 The hypertensive animals also had elevated plasma AVP levels, a finding that has been reported previously by others 1 -2 and is probably due to an increased synthesis of AVP in the supraoptic and paraventricular nuclei of the hypothalamus.…”
Section: Resultssupporting
confidence: 87%
“…On the contrary, high-salt intake alone did not affect the cAMP generation in response to AVP. This finding is in agreement with that was observed by previous investigators, in which dietary salt intake in the absence of DOCA had no effect on the cAMP response to AVP (19). Taken together, basal as well as stimulated adenylate cyclase activity may be specifically augmented by DOCA.…”
Section: Reprintssupporting
confidence: 93%
“…However, it has been shown that DOCA-induced hypertension is dependent on excess dietary salt (19). Furthermore, a significant hypertension is lacking in syndrome of inappropriate antidiuretic hormone, although AQP2 expression is increased (22,23).…”
Section: Aquaporin-2 Water Channels In Hypertension 537mentioning
confidence: 99%
“…Recently it has been shown that the enhanced vasopressin-stimulated accumulation of cyclic adenosine monophosphate in cortical collecting tubules seen in DOC-salt-treated Wistar rats is also present in DOCsalt-treated WF rats, despite their resistance to hypertension. 20 This study provides additional evidence that some physiological responses to mineralocorticoids are preserved in WF rats.…”
Section: Resultsmentioning
confidence: 57%